microRNAs associated with the pathogenesis and their role in regulating various signaling pathways during Mycobacterium tuberculosis infection - Chauhan, Devendra; Davuluri, Kusuma S. (Frontiers in Cellular and Infection Microbiology, 2022)
Despite more than a decade of active study, tuberculosis (TB) remains a serious health concern across the world, and it is still the biggest cause of mortality in the human population. Bacterial pathogens successfully recognise, respond to, and adapt to a wide range of hostile circumstances offered by the mammalian host during infection. This high level of adaptability necessitates a strong regulation of their physiological and metabolic characteristics. Furthermore, virulence factors such as host invasion, colonisation, and survival must be properly coordinated by the pathogen at all times throughout infection, despite the host's immune responses and antimicrobial treatment (Honeyborne et al., 2015). This can only be accomplished by close synchronisation of gene expression. Efforts to understand the molecular basis of mycobacterial pathogenesis in order to discover therapies that prevent or resolve illness rely on the bacterial capacity to adjust their metabolism and replication in response to various environmental cues. An extensive literature details the transcriptional alterations in response to in vitro environmental stressors, macrophage infection, and human illness (Ostrick et al., 2020). Various studies have recently revealed the finding of several miRNAs that are believed to play an important role in the regulatory networks responsible for adaptability and virulence in M.tb. We highlighted the growing data on the existence and quantity of several forms of miRNAs in M.tb and considered their possible relevance to disease aetiology and discuss how the miRNA-based signalling pathways regulate bacterial virulence factors.